2019
DOI: 10.18821/0016-9900-2016-95-1-106-112
|View full text |Cite
|
Sign up to set email alerts
|

On the question of the application of the prediction of the evolution of health risk in hygienic assessments

Abstract: In the paper there are described examples of the practical implementation of methodological approaches to the assessment of evolution of the health risk under exposure to a set of environmental factors. In the hygienic assessment of the dynamics of health risks for citizens, residing near a major airport (about 500 takeoffs and landings per day), there were revealed high risks of disorders of the cardiovascular and nervous system. The difference between the risks emerging under the exposure and without the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Based on the results of the hygiene and environmental studies the priority environmental factors were identified that had the greatest differences in concentrations and health risk criteria [6,17,19]. The high proportion of urban residents (71,4%) are marking the impact on their health adverse environmental factors environment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of the hygiene and environmental studies the priority environmental factors were identified that had the greatest differences in concentrations and health risk criteria [6,17,19]. The high proportion of urban residents (71,4%) are marking the impact on their health adverse environmental factors environment.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of clinical-statistical and medical-sociological analysis the prevalence of chronic diseases and specific clinical symptoms was studied among the surveyed urban residents with their classification by health groups [2]. The revealed information importance criteria were used to evaluate the severity of the impact of risk factors on the integral indicator of health-related quality of life [5,19]. A screening questionnaire [3] was conducted the specialized questionnaire WHO "Burden of major Respiratory Diseases Who Survey" (GARD program) among a representative sample (3032 people) of the population in administrative districts of St. Petersburg with different severity of ecological trouble (by atmospheric air indicators).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Разрабатываются новые подходы к оценке риска продукции, в том числе использующие методы математического моделирования нарастания (эволюции) рисков во времени [21]. При этом новые методы в полной мере реализуют общепринятые принципы оценки риска и релевантные токсикологические и эпидемиологические данные.…”
unclassified
“…Experts are creating new approaches to assessing product risks including those that incorporate mathematic modeling for risk evolution over time [21]. And these new approaches fully implement conventional risk assessment principles and relevant toxicological and epidemiologic data.…”
mentioning
confidence: 99%